PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI BARANG MEWAH DI E-COMMERCE - Ratna Kartika Indraswari (2022)
Trading activities in the community have grown very rapidly. The growth of internet-based technology known as e-commerce has influenced this. E-commerce is a type of trade with its own set of characteristics, such as cross-national trading via the internet and the absence of face-to-face meetings between sellers and purchasers. On the one hand, this situation benefits consumers because they have more options for purchasing products and services, but on the other hand, consumer rights violations are more risky due to the specific characteristics of ecommerce. Therefore, legal protection for consumers is very much needed in ecommerce transactions. Legal protection for consumers is regulated by Law No. 8 of 1999 concerning Consumer Protection. This law is expected to guarantee legal certainty for consumers in e-commerce transactions. In connection with this, in this thesis three issues are raised, first whether the Consumer Protection Act No. 8 of 1999 can protect consumers in conducting e-commerce transactions, secondly how is the legal protection for consumers of luxury goods that should be regulated in e-commerce transactions, third What problems arise in the legal protection of consumers of luxury goods in e-commerce transactions and how to overcome them. The methodology used in this study uses an empirical normative approach, because it is a legal research regarding the enforcement or implementation of normative legal provisions in action on every particular legal event that occurs in society. Based on the discussion of the research results, it can be concluded first that the consumer protection law No. 8 of 1999 has not been able to protect consumers in e-commerce transactions because of the limited understanding of business actors who are only specifically in the territory of the Republic of Indonesia. And the limitations of consumer rights regulated in Law on Consumer Protection. Second, legal protection for consumers that should be regulated includes legal protection from the side of business actors, from the consumer side, from the product side, and from the transaction side.